Mental Health Services for Serious Mental Illness: Scoping Review of Randomised Controlled Trials - Pablo Roson Rodriguez; Xiao Chen; Marcelo Arancibia; Eva Madrid; Farhad Shokraneh; Clive E. Adams; Juan Víctor Ariel Franco (Nursing Open)
ABSTRACT Aims This review aims to classify the evidence from randomised controlled trials (RCTs) on mental health services (MHS) for people with serious mental illness (SMI) available in the Cochrane Schizophrenia Group's (CSzG) specialised register. Design Scoping review. Methods We retrieved and screened RCTs of service‐level interventions considering non‐pharmacological approaches for mental healthcare of the CSzG register. We classified and collected the main characteristics of the RCTs using a customised data extraction and charting form based on DESDE‐LTS classification. Results We included 233 out of 262 total trial registries. Most of the studies were conducted in China, 136 (58%), 57 (24%) North America and 26 (11%) Europe. We classified the studies as ambulatory assistance 80 (34%), day services/out‐patient care 38 (16%), residential services 44 (19%), accessibility to care 19 (8%), information/assessment 39 (17%), self‐help and voluntary help 10 (4%), e‐health 52 (22%), and discharge services 17 (7%). Conclusions We found a large number of trials that investigated the effects of mental health services for people with SMI. Trials classification was difficult due to the poor report of the characteristics of these complex interventions. This database can be used to plan and prioritise systematic reviews according to the needs of stakeholders. Relevance Statement The study is of interest to mental health nursing because it studies the different services in which nurses play a fundamental role with implications in the nursing practice, education, research or leadership and management.